Analisis Pesan Dakwah Maher Zain dalam Sholawat Burdah di Channel Youtube - Wati, Dini Atika; Arianti, Qori Hajidah; Qoimah, AI Hidayahtul Mus; Zuhriyah, Luluk Fikri; Purnomo, Ryan (Kamaya: Jurnal Ilmu Agama, 2024)
This study aims to analyze the signs and messages of da'wah in the Burdah prayer presented on Maher Zain's YouTube channel. The background of this research is the importance of understanding the meaning of signs in modern da'wah media as a means of conveying Islamic values. The formulation of the problem includes three main aspects, namely the meaning of the sign in the Burdah prayer, the connotative and denotative meaning of the da'wah message, and the essence of the da'wah message contained. This study uses a graphical subjective examination technique with an information examination method that involves in-depth data collection, parsing, and analysis. The focus of the research includes the identification of signs, implied meanings, suggestive signs, denotative signs, and symbols in the Burdah prayer. The results of the study show that: first, the signs in the Burdah prayer, such as the symbol of the robe and the black robe, have an important meaning as a medium for conveying the message of protection and spiritual elegance. Second, the connotative and denotative meaning of the da'wah message represents the majesty of the Prophet Muhammad PBUH and the importance of prayer for mercy and salvation from Allah. Third, the da'wah message contained in the Burdah prayer includes the teaching values of aqidah, ethics, and sharia, which are the core of Islamic teachings. The conclusion of this study confirms that the Burdah prayer has a depth of da'wah message that is relevant to modern life, combining elements of art and spirituality to convey the teachings of Islam. This research contributes to the development of da'wah communication studies through digital media.